The the formation of work teams: a strategic step to fly higher and further (Dissertare, 2022)
The great structural and technological changes that have occurred in organizations in recent decades –regardless of the sector to which these organizations belong– have generated a great impact on the way of working and solving problems, which is part of the challenges of human management in the 21st century, especially with regard to teamwork. This essay seeks to highlight various relevant aspects of work teams in the digital age and in the complex post-pandemic stage. Among these aspects are: the distinctive characteristics of work teams; the similarities and differences between work groups and teams; the competencies that distinguish the members of the latter, as well as their advantages and usefulness. The qualitative methodological approach was used with a documentary design and an extensive bibliographic review, supported by critical analysis. It was concluded that contemporary organizations need today, more than ever, the development of transversal skills in their collaborators, in order to favor their integration into teamwork, for the resolution of problems and challenges that cannot be solved through individual effort due to their complexity. In addition, the importance of emotional connection is highlighted, in order to establish an interdependence that generates high-performance teams, which is also applicable to virtual environments.
Keywords: teams; high performance teams; groups; synergy; teamwork